Anxiety and depression on the liver transplant waiting list: a case for psychological prehabilitation?. (1st July 2020) - Tavabie, Oliver; McKie, Paul; Webzell, Ian; Beckford, Racquel; Menon, Krishna; O'Grady, John; Aluvihare, Varuna R
Abstract : Introduction: Anxiety and depression in patients awaiting liver transplantation are associated with worse clinical outcomes. However, optimising patient mental health is not routinely addressed in pre-transplant care. Aims: To understand the prevalence of anxiety and depression in patients awaiting transplantation and their access to pharmacological and psychological therapies. Methods: Patients awaiting transplantation were offered screening for anxiety and depression using the Hospital Anxiety and Depression Screening (HADS) tool. Data pertaining to patient demographics and previous treatment for anxiety and depression were recorded and analysed. Findings: Over 50% of patients recorded abnormal scores for anxiety and depression. Of the 19 patients screened, 42% had received treatment for either disorder, and most found the intervention unhelpful due to lack of follow-up appointments and limited understanding of their underlying chronic liver disease. There was a significant association between female sex and screening positive for depression. Conclusion: Anxiety and depression are prevalent in patients awaiting liver transplantation. The integration of a psychologist into the transplantation multidisciplinary team may improve patient outcomes.